Performance Analysis of Genetic Zone Routing Protocol Combined With Vertical Handover Algorithm for 3G-WiFi Offload - Setiyo Budiyanto; Muhammad Asvial; Dadang Gunawan (LPPM ITB, 2014)
In the deployment scenario of multiple base stations there is usually a deficiency in the routing protocols for load balancing in the wireless network. In this study, we propose a routing algorithm that can be implemented inMobile Adhoc Networks (MANETs) as well as third-generation (3G)